Evaluation of Artificial Intelligence (AI) Scribes in Medical Practice: Cross-Regional Analysis - Anju Soni; Ian Treasaden (BJPsych Open)
Aims: This study aimed to evaluate the implementation of AI scribes in medical practice across Australia and England, focusing on assessing current adoption rates, measuring awareness of perceived benefits and potential risks and developing recommendations for safe and effective deployment.